Experimental study of the pharmacological activity of new azaheterocycles derivatives: A literature review - Malika Khaiitova; Aida Seitaliyeva; Elmira Satbayeva; Daniya Serdalieva; Talgat Nurgozhin (National Scientific Medical Center, 2022)
Diseases associated with the pathology of the cardiovascular system are one of the key causes of death all over the world. In particular, arrhythmia may entail the most severe complications, including unexpected death. With high-tech advances, antiarrhythmic drugs remain an integral part of both therapy and prevention. However, the existing arsenal of drugs often does not provide the necessary clinical effect, and therapy is associated with a high risk of severe adverse events. Another significant problem today is the administration of low-toxic drugs that provide effective anesthesia with a sufficient depth and duration of action. Currently, there is also the problem of the limited effectiveness of many drugs with antitumor, antimicrobial, antiviral, antifungal, anti-inflammatory activity and action on the central nervous system. One of the solutions to address the existing problems in these areas is the search and study of compounds that may serve as a basis for the development of new drugs. Given the membrane-stabilizing action by influencing ion channels, new derivatives of azaheterocycles- compounds of piperidine and piperazine are of particular interest in these areas of medicine. According to domestic studies, new piperidine derivatives during screening and in-depth studies showed pronounced local anesthetic activity during infiltration and conduction anesthesia. The results of a number of studies confirm the presence of antiarrhythmic activity in piperidine derivatives. Experimental data on the synthesis and study of the pharmacological activity of new derivatives of piperidine and piperazine in world practice prove their promise for the creation of drugs in various fields of medicine in the future.